Faddeev-Jackiw quantization of Proca Electrodynamics - Pimentel, B. M. [UNESP]; Zambrano, G. E.R. (Elsevier, 2015)
The generalized symplectic formalism quantization method is employed to study the gauge invariance Proca electrodynamics theory. We show that the zero modes of the symplectic matrix are the generators of the gauge transformation. After fixing the gauge, the generalized brackets are calculated.
Keywords: Constrained systems; Faddeev-Jackiw method; Field theory; Proca electrodynamics